2012
DOI: 10.4103/0974-9233.92124
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of retinopathy of prematurity and risk factors in the South-Western Region of Iran

Abstract: Aims:The aim of this study was to report the incidence of retinopathy of prematurity (ROP) and the contribution of various risk factors to ROP in the south-western region of Iran.Material and Methods:This cross-sectional case-control series reviewed all low birth weight (LBW, ≤2000 g) neonates and/or neonates less than 32 weeks gestational age who had been hospitalized in the Neonatal Intensive Care Unit from 2006 to 2010. The cohort was divided into infants without ROP (nonROP group) and infants with ROP (ROP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 23 publications
5
29
0
Order By: Relevance
“…Bassiouny et al 27 reported that lower BW, GA, apnoea, blood transfusion, mechanical ventilation, metabolic acidosis, intraventicular haemorrhage and sepsis were associated with development of ROP. Signifi cant association of sepsis with the presence of ROP (p= 0.002) in this study is similar to reports from other part of world [28][29][30] , indicating that there exists inadequate neonatal care in NICU which warrants improvement.…”
Section: Discussionsupporting
confidence: 79%
“…Bassiouny et al 27 reported that lower BW, GA, apnoea, blood transfusion, mechanical ventilation, metabolic acidosis, intraventicular haemorrhage and sepsis were associated with development of ROP. Signifi cant association of sepsis with the presence of ROP (p= 0.002) in this study is similar to reports from other part of world [28][29][30] , indicating that there exists inadequate neonatal care in NICU which warrants improvement.…”
Section: Discussionsupporting
confidence: 79%
“…Measures of morbidity used particularly in community based studies included; need for hospitalisation and prevalence of wheezing and pneumonia [ 23 ], number of routine and additional clinic visits in the post natal period [ 19 ] or a pictorial diary with specific measurements of diarrhoea and ways of measuring body temperature and respiratory rate [ 17 ]. Studies with an emphasis on facility based care used proxy measures for morbidity such as need for transfer to NICU [ 49 ], length of time in NICU [ 70 , 71 , 72 ] time spent in oxygen [ 73 ] and time spent on ventilator [ 41 , 74 – 76 ], number of routine and additional clinic visits in the post natal period [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these facility based studies report an increased risk of morbidity in preterm infants compared to babies born at term. This includes increased risk of respiratory distress syndrome (RDS) [ 52 , 59 , 102 , 103 ], broncho-pulmonary dysplasia (BPD) [ 68 , 97 , 104 108 ], retinopathy of prematurity (ROP) [ 73 , 101 , 106 , 109 ] intraventricular haemorrhage (IVH) [ 72 , 110 ], periventricular leukomalacia (PVL) [ 111 ] and cerebral palsy [ 55 , 58 , 112 ]. Studies are however not comparable due to differences in diagnostic approach and level of care available in the different settings.…”
Section: Resultsmentioning
confidence: 99%
“…[23456789] The third important risk factor in our study is prolonged oxygen exposure by invasive or noninvasive ventilation, and by nasal cannula, that was proportionately increasing the risk of ROP occurrence. The premature neonate is developmentally unprepared to the oxygen-rich extrauterine life because of an impaired antioxidant defense system.…”
Section: Discussionmentioning
confidence: 87%